Early goal-directed therapy: what do we do now? - Levy, Mitchell M (Crit Care, 2014)
The meta-analysis of early goal-directed therapy (EGDT) by Gu and colleagues in the previous issue of Critical Care adds to the ongoing controversy about the value of EGDT for resuscitating patients with severe sepsis and septic shock. The results of the ProCESS (protocolized care for early septic shock) and ARISE (Australasian resuscitation in sepsis evaluation) trials failed to demonstrate any benefit of EGDT or protocolized resuscitation when compared with ‘usual care’. The questions are the following: What is ‘usual’ care? What is ‘real world’ care? Do the results of a robust and well-conducted randomized controlled trial - in which many patients may be excluded for a variety of reasons - reflect the care given to patients on a daily basis in our emergency departments and intensive care units? Of course, there are no obvious answers to these questions, and many clinicians look forward to managing these patients without protocols. For now, the data do seem to support the management of patients with septic shock without mandated central lines or protocols. Does this mean we should go back to the era of ‘do whatever you want’? No consensus exists among clinicians regarding optimal hemodynamic monitoring, and to date no method has been proven to be superior. Given the amount of fluids given prior to randomization in the ProCESS and ARISE trials, ‘usual care’ appears to now include aggressive, early fluid resuscitation with at least 20 mL/kg of crystalloid and rapid administration of appropriate antibiotics. Certainly, this reflects the impact of the original trial by Rivers and colleagues and the broad-based implementation of the Surviving Sepsis Campaign Guidelines and bundles. If this continues to define ‘usual care’, then perhaps it is no longer necessary to mandate specific protocols for resuscitation, as it appears that standard sepsis management has evolved to be consistent with published protocols.